Protein kinase inhibitors from Indonesian Sponge Axynissa sp. - Triana Hertiani; Ru Angelie Edrada-Ebel; Michael Kubbutat; rob W.M. van Soest; peter Proksch (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
A research about inhibitory activity on various cancer related protein kinases of several marine sponges collected in Indonesia was performed. This study aims were to isolate and to identify structures of biologically active sponge metabolites.A combination of a chemically-and biologically driven approach for drug discovery was employed. Sponge extracts were tested by protein kinase inhibitory assay by in vitro method in parallel to the usage of TLC, and HPLC coupled to UV spectrophotometry and mass spectrometry to isolate the chemically most interesting substances. Structure identification of active compounds was performed by using NMR spectroscopy and massspectrometry methods.This study showed that only Axynissa sp. fractions were found active in protein kinase inhibitory assay. Two bisabolene type sesquiterpenoids, (+)- curcuphenol (1) and (+)-curcudiol (2) were identified as active compounds from the sponge. Compound 1 showed SRC protein kinase inhibition with an IC50value of 7.8 μg/mL while 2 inhibited FAK with an IC50 value of 9.2 μg/mL.Key words: protein kinase inhibitor, Axynissa sp.